Review of bean production in Uganda outside the highland and fertile crescent zones - Male-Kayiwa, B.S. (International Center for Tropical Agriculture, 1991)
Beans are grown and consumed in all of the 34 districts of Uganda. Areas outside the highland and fertile crescent zones account for over 60 percent of the country's production. Increased production over the past 10 years has been through area expansion rather than increased yield. Production constraints include diseases and pests, poor yielding varieties, land limitations, soil fertility, water stress, and poor marketing system. Beans are consumed both in the fresh and dry states as a sauce accompanying the staple food. The most common bean dish is cooked in a mixture with either bananas or cassava. In the central and eastern regions, beans are consumed in a mashed form with sweet potatoes, while in the northern region they are mixed as a sauce with other grains such as simsim and groundnuts. (AS)